Mutations in fas associated with human lymphoproliferative syndrome and autoimmunity - Rieux-Laucat, Frédéric; Le Deist, F.; Hivroz, C.; Roberts, I. A. G.; Debatin, Klaus-Michael; Fischer, A.; de Villartay, J. P. (Science, 1995)
Fas (also known as Apo1 and CD95) is a cell surface receptor involved in apoptotic cell death. Fas expression and function were analyzed in three children (including two siblings) with a lymphoproliferative syndrome, two of whom also had autoimmune disorders. A large deletion in the gene encoding Fas and no detectable cell surface expression characterized the most affected patient. Clinical manifestations in the two related patients were less severe: Fas-mediated apoptosis was impaired and a deletion within the intracytoplasmic domain was detected. These findings illustrate the crucial regulatory role of Fas and may provide a molecular basis for some autoimmune diseases in humans.